2007
DOI: 10.1515/crelle.2007.048
|View full text |Cite
|
Sign up to set email alerts
|

Explicit formulas for Hecke operators on cusp forms, Dedekind symbols and period polynomials

Abstract: Abstract. Let S w+2 be the vector space of cusp forms of weight w + 2 on the full modular group, and let S * w+2 denote its dual space. Periods of cusp forms can be regarded as elements of S * w+2 . The Eichler-Shimura isomorphism theorem asserts that odd (or even) periods span S * w+2 . However, periods are not linearly independent; in fact, they satisfy the Eichler-Shimura relations. This leads to a natural question: which periods would form a basis of S * w+2 . First we give an answer to this question. Pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Then in [8,12] it is shown that the values of r m (R n ) can be expressed in terms of the Bernoulli numbers for integers m and n with opposite parity satisfying 0 m 2k − 2 and 1 n 2k − 3. In [7], by considering the natural correspondence of S 2k (SL(2, Z)), its dual, and the space of Dedekind symbols, the first author of the present article found bases for S 2k (SL(2, Z)) in terms of R n , which in turn give explicit expression for Hecke operators in terms of Bernoulli numbers and sum-of-divisor functions. For the case Γ 0 (2), this is done in [8] with a different approach.…”
Section: Introduction and Statements Of Resultsmentioning
confidence: 90%
“…Then in [8,12] it is shown that the values of r m (R n ) can be expressed in terms of the Bernoulli numbers for integers m and n with opposite parity satisfying 0 m 2k − 2 and 1 n 2k − 3. In [7], by considering the natural correspondence of S 2k (SL(2, Z)), its dual, and the space of Dedekind symbols, the first author of the present article found bases for S 2k (SL(2, Z)) in terms of R n , which in turn give explicit expression for Hecke operators in terms of Bernoulli numbers and sum-of-divisor functions. For the case Γ 0 (2), this is done in [8] with a different approach.…”
Section: Introduction and Statements Of Resultsmentioning
confidence: 90%
“…Fukuhara showed that there is a one-to-one correspondence among the spaces S w+2 , E ± w and U ± w (see [6,8,9]). …”
Section: Furthermore We Define Ementioning
confidence: 99%
“…To state the result in [3] we need the following notation and convention: form a basis for S * 2k . Next we will display a basis for S 2k .…”
Section: Preliminariesmentioning
confidence: 99%